The impacts of localised council tax support schemes - Stuart Adam; Robert Joyce; Thomas Pope (Institute for Fiscal Studies (IFS), 2019)
In April 2013, council tax benefit (CTB), which provided help for low-income households with their council tax, was abolished. In its place, local authorities (LAs) in England were charged with designing their own council tax support (CTS) schemes for those of working age - though they were obliged to provide a centrally determined (and largely protected) level of support for pensioners. With reduced funding made available to them by central government, most LAs chose CTS schemes that were less generous than the CTB system they were replacing, with some low-income households having to pay council tax for the first time and others seeing their tax liabilities increase. CTS remains a significant part of our system of means-tested support. Across Great Britain, it was paid to 4.9 million households in 2017-18 - more than any other meanstested payment. It cost LAs 4.1 billion, which represents an aggregate reduction of about 11% of gross council tax bills (leaving them with 33 billion of net council tax revenue). Spending on the 2.4 million working-age claimants in England - the focus of this report, since it is their entitlements that now vary between LAs - came to 1.8 billion, implying an average award for those claimants of 770 per year. Five years on from the localisation and funding cut for CTS, this report looks at how LAs' CTS schemes have evolved since they were first introduced, and at the changing effects of these scheme choices on claimants and on LAs.
Keywords: 330